IMPROVING NARRATIVE TEXT WRITING SKILL THROUGH DICTATION TOWARDS AUDITORY AND VISUAL LEARNERS (Universitas Negeri Semarang, 2012)
Tesis ini mendiskusikan tentang diktasi, listening, dan penulisan naratif. Peneliti menggunakan factorial design dalam memilih latar belakangnya. Penelitian ini merupakan penelitian quantitative. Metode yang digunakan adalah studi eksperimental. Sebelum penelitian dilakukan peneliti membagi kelas menjadi kelas eksperimen dan control. Tes diklasifikasikan kedalam auditory dan visual learner. Penelitia mencoba menggunakan ANOVA untuk mendapat data final. Oleh karena beberapa karakter ANOVA yang menyebabkan data distribusi tidak normal, peneliti menggunakan Kurskall-Walls tes dilanjut dengan pos-hoc ANOVA untuk menemukan signifikansi dari strategi diktasi dan listening. Hasil menunjukan bahwa diktasi lebih efektif untuk mengajar naratif dibandingkan listening.This thesis discusses about the dictation, listening and narrative writing. Learning styles are needed in this area, so, the researchers gets the data of learning styles first before she decides to collect the data and analyze it. While choosing the background of the study the researcher uses factorial design. There are seven factors which become the problems of the study for this research. This research is quantitative research. The method used in this research uses experimental study, while there are experimental and control group. Before the researcher decides to do pre test and post test for both groups, the researcher uses learning styles test. The test classifies each group into auditory and visual learners. The researcher tried to use ANOVA to get the final data. Because of some factors that become the characteristics of ANOVA itself, there is not normal distribution data appeared in the research, so the researcher uses Kurskal-Walls test and continually with pos-hoc ANOVA to find the significance of strategies between dictation and listening. Based on the result of Pos-hoc ANOVA that has been done, it proves that dictation is more effective way for teaching narrative writing than listening. It is for both visual and auditory learners.